AB0245 PREDICTORS OF BIOLOGIC THERAPY DISCONTINUATION IN RHEUMATOID ARTHRITIS PATIENTS AFTER REMISSION ACHIEVEMENT: A MONOCENTRIC OBSERVATIONAL STUDY FROM BIOLOGIC APULIAN REGISTRY (BIOPURE). (June 2019) - Fornaro, Marco; Cacciapaglia, Fabio; Lopalco, Giuseppe; Venerito, Vincenzo; Schiraldi, Sante; Renna, Daniela; Laselva, Gaetana; Scioscia, Crescenzio; Lapadula, Giovanni; Iannone, Florenzo; ,
Abstract : Background: Thanks to biologic therapies, disease remission in Rheumatoid Arthritis (RA) patients is not a wishful thinking but an achievable goal. Nevertheless, some patients experienced treatment discontinuation after obtaining disease remission. EULAR recommendations suggest to suspend steroids as soon as possible 1, but in real life-setting this point is not always hold in esteem. Objectives: The objective of our study was to assess the impact of steroids on the long-term drug survival and the possible predictors of drug discontinuation in RA patients who achieved Simplified Disease Activity Index (SDAI) remission at 1-year upon treatment with a first biologic disease modified anti-rheumatic drug (bDMARD). Methods: Data of RA patients naïve to bDMARDs, registered in Biologic Apulian Registry (BIOPURE) between 1st January 2008 to 31st December 2017, were retrospectively analysed. Demographic and clinical data of all RA patients were acquired at the initiation of first bDMARDs ("screening-time") and after 1-year follow-up ("baseline-time"). The inclusion criterion in this study was the achievement of SDAI remission (SDAI ≤ 3.3) at 1 year of treatment with a first bDMARD. At "baseline-time", RA patients on SDAI remission were divided, according to steroid administration, into concomitant "steroid-no" and "steroid-yes" groups. Drug retention rate and mean survival time (MST) were estimated using Kaplan-Meier (K-M) life-table method. Estimated hazard ratios (HRs) of discontinuing bDMARD were assessed by performing a multivariate Cox-regression analysis with stepwise backward methods. Results: 216 RA patients started their first bDMARDs between 1st January 2008 to 31st December 2017. Among these, 86 (39.8%) patients achieved SDAI remission at 1-year of whom 54 (62.8%) were steroid free while 32 (37.2%) were still intaking low-dose steroids (mean 3.8 mg/die; SD ±1.4). Considering patients who achieved SDAI remission at "baseline-time", global drug retention was 81.4% [MST=88.5 (95% CI: 80-97) months], higher for "steroid-no" patients [90.7%, MST=98.2 (95% CI: 89-107) months] than "steroid-yes" ones [68.8%, MST=68.9 (95% CI: 57-81) months] (long rank 7.086, p=0.008) (Figure 1 ). This difference was also seen when drug discontinuation by ineffectiveness was calculated [96.1%, MST=103 (95%CI: 96-110) months vs 72.4%, MST= 70.6 (95%CI 57-84) months, long rank 10.101, p=0.001], but not by adverse events. Moreover, no steroid administration (HR = 0.31, 95% CI:0.10-0.93) and concomitant Methotrexate therapy (HR = 0.34, 95% CI:0.12-0.98) were independently associated with low risk of bDMARDs interruption after the achievement of SDAI remission. Conclusion: This study provided evidence that, among RA patients who achieved SDAI remission, those who stopped steroids and continued combination therapy with MTX had a very long drug survival with just the first bDMARD in a real-life setting. These results can help rheumatologists to precociously select RA patients who might start a tapering or spacing strategy of biologic drug. Reference: [1] Smolen JS, Landewé R, Bijlsma J, Burmester G. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2016 update. Ann Rheum Dis. 2017Jun;76(6):960-977. Disclosure of Interests: Marco Fornaro: None declared, Fabio Cacciapaglia: None declared, Giuseppe Lopalco Speakers bureau: SOBI, BMS, vincenzo venerito: None declared, Sante Schiraldi: None declared, Daniela Renna: None declared, Gaetana Laselva: None declared, Crescenzio Scioscia Speakers bureau: Abbvie, Giovanni Lapadula: None declared, Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work